A prospective case series for a minimally invasive internal fixation device for anterior pelvic ring fractures - Hoskins, W; Bucknill, A; Wong, J; Britton, E; Judson, R; Gumm, K; Santos, R; Sheehy, R; Griffin, X (BioMed Central, 2017)
Background External fixation is commonly used as a means of definitive fixation of pelvic fractures. Pin site infection is common, with some cases of osteomyelitis and inpatient nursing can be challenging. The aim of this study is to report the outcomes and complications of an alternative minimally invasive technique, known as INFIX, utilising spinal pedicle screws inserted into the supra-acetabular bone and connected by a subcutaneous rod. Methods A single-centre prospective case series was performed. The primary outcome measures were fracture stability and displacement at time of implant removal and intra- and post-operative complications. Results Twenty-one patients were recruited, with 85.7 % of fractures being lateral compression type. Mean follow-up was 342 days. Mean application time was 51 min (range 44–65). Nineteen were removed electively, with mean time to removal 109 days. All cases were stable with no displacement. Two cases were removed emergently, one due to wound infection and the other due to lateral femoral cutaneous nerve neuropathic pain. Twelve patients sustained a lateral femoral cutaneous nerve palsy, with 20/42 nerves being affected. Improvement in all lateral femoral cutaneous nerve symptoms were reported with removal. Nine patients developed asymptomatic heterotopic ossification, and there were three deep infections and one symptomatic due to the bar. Conclusions Minimally invasive internal fixation with the INFIX for anterior pelvic ring fractures is an alternative to anterior external fixation. However, a higher rate of lateral femoral cutaneous nerve palsy is noted, and the implant is not well tolerated by all patients. Further studies are required to define fracture types and patients best suited to the technique and how LFCN complications may be minimised.